2017
DOI: 10.14814/phy2.13270
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic changes in rat soleus muscle after high-fat high-sucrose diet

Abstract: The effects of obesity on different musculoskeletal tissues are not well understood. The glycolytic quadriceps muscles are compromised with obesity, but due to its high oxidative capacity, the soleus muscle may be protected against obesity‐induced muscle damage. To determine the time–course relationship between a high‐fat/high‐sucrose (HFS) metabolic challenge and soleus muscle integrity, defined as intramuscular fat invasion, fibrosis and molecular alterations over six time points. Male Sprague‐Dawley rats we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…As previously shown using the same diets (Collins et al 2016, Collins et al 2017Rios et al 2019), animals in the high-fat high-sucrose group reached significantly greater body mass and percentage body fat compared to control group animals, indicating the presence of obesity. The high-fat high-sucrose diet did not affect lean body mass development but rather, led to greater fat content.…”
Section: Animal Morphologysupporting
confidence: 75%
See 1 more Smart Citation
“…As previously shown using the same diets (Collins et al 2016, Collins et al 2017Rios et al 2019), animals in the high-fat high-sucrose group reached significantly greater body mass and percentage body fat compared to control group animals, indicating the presence of obesity. The high-fat high-sucrose diet did not affect lean body mass development but rather, led to greater fat content.…”
Section: Animal Morphologysupporting
confidence: 75%
“…For the first 7 weeks, animals in the dietary-induced obesity group (n=8) were fed a high-fat high-sucrose diet (Dyets 103915) consisting of 24% protein, 20% fat, and 45% protein, and for the second half of the study weeks 8-14) the diet (Dyets 102412) was comprised of 15-20% protein, 40% fat, and 40-45% carbohydrates (>97% of carbohydrates from sucrose). Obesity was induced over a fourteen week period, a time frame that has been shown previously to result in obesity in adult rats (Collins et al 2016, Collins et al 2017Rios et al 2019). The diet began at weaning and was maintained through adolescence and into adulthood.…”
Section: Obesity Inductionmentioning
confidence: 99%
“…Also, there is a lack of data describing the effect of obesity on muscle integrity, and a lack of consistent protocols to assess muscle strength (Tomlinson et al, 2016 ). However, data from our lab (Collins et al, 2016a , c , 2017b ) and others, in rodents (Ciapaite et al, 2015 ) and large mammals (Clark et al, 2011 ), have demonstrated deleterious alterations in muscle structural integrity with metabolic disturbance. Computational approaches modeling the gastrocnemius muscle have demonstrated that whole-muscle force is dependent on muscle integrity, specifically regarding reductions of muscle force due to intramuscular lipid (Rahemi et al, 2015 ).…”
Section: Obesity and Impact On Muscle Integritymentioning
confidence: 66%
“…Work from our laboratory has demonstrated that the oxidative soleus muscle is protected against HFS-induced damage over short-term and long-term exposures in a rat model (Collins et al, 2017b ; Figure 4 ). By 3-days on HFS, dynamic increases in mRNA levels for superoxide dismutase (SOD2) in HFS animals implicate compensatory oxidative stress scavenging in the soleus muscle compared to control animals.…”
Section: Obesity and Impact On Muscle Integritymentioning
confidence: 98%
“…In this respect, a study using mixed high‐fat and sucrose diet in rats to evaluate muscle performance in obesity, showed that even though the quadriceps muscle was functionally attenuated, the slow twitch soleus muscle was resistant to diet‐based muscle alteration (Collins et al. ). The alteration of CSA of type IIB and IIX fibers on HFD seems to be of relevance to the muscle phenotype as well as to its metabolic activity.…”
Section: Discussionmentioning
confidence: 99%